Chrysin attenuates hyperglycemia associated with hepatorenal and glycoprotein abnormalities via regulation of glucose metabolism in HFD/STZ- induced diabetic rats - R. Sundaram; K. Muthu (Elsevier, 2024)
Background: Flavonoids like chyrsin, which are abundant in plant extracts, honey, and bee propolis, have antiviral, anti-cancer, anti-bacterial, anti-inflammatory, anti-allergic, anti-mutagenic, anti-anxiolytic, and other therapeutic uses. However, no research has been published on how chrysin protects rats against HFD/STZ- induced changes to the glycoprotein moiety via controlling the metabolism of glucose. Methods: For two weeks, albino male wistar rats were fed a high-fat diet in order to develop diabetes. Upon two weeks, a low dosage of streptozotocin (35 mg/kg, diluted in 0.1 M sodium citrate buffer, pH 4.5) was administered into the animals after they had been fasted for the whole night. Blood glucose, insulin, hepatic, and renal indicators were analyzed using commercially available diagnostic kits, and other parameters were ascertained biochemically. Results: For 30 days, high-fat diet- and streptozotocin-induced diabetic rats were given 40 mg/kg b.w./day of chrysin, which significantly reduced blood glucose, homeostatic model assessment of insulin resistance, glycogen phospharylase, hepatic and renal markers, and increased insulin, glycogen content, and glycogen synthase levels. Conclusion: However, the altered activity of the glycoprotein components and the carbohydrate metabolic enzymes was restored upon chrysin administration. On several criteria, the chrysin's effect was similar to that of metformin. Chrysin is therefore a potential antidiabetic agent.